Conferencing the international at the World Pacifist Meeting, 1949. (November 2015) - Hodder, Jake
Abstract: This paper considers how the act of conferencing was central to imagining, negotiating and contesting post-war pacifism as an internationalist project. The paper contends that internationalism and the international conference are inexorably entwined. Through the study of conferencing geographers can explore the situated historical and political geographies of internationalism which belies its otherwise transcendent or universalist claims. A reading of the 1949 World Pacifist Meeting in India is used to make two key arguments. Firstly, it shows how conferences operate as stage-managed events through which to script and perform an alternative vision of internationalism. Half conference, half pilgrimage, the global composition of delegates was arranged to suggest a space 'singularly free from any sense of geographical limitation'. Yet total immersion in the rich cultural and historical context of India marked an uneven internationalist arena, where the 'Land of Gandhi' was held with unparalleled revere. Secondly, whilst geographers and others have turned to conferencing in recent years, this has largely been contained to 'summitry' and high-end diplomacy. This paper calls for geographers to consider a wider range of conferencing spaces and practices, and argues that studying 'other conferences' by necessity opens up consideration of other forms of internationalism. The paper concludes that the World Pacifist Meeting's delegates imagined an alternative form of internationalism, exemplified by a alternative form of international conference, which challenged state-centric readings of global power relations.